World past to world present - Stearns, Peter N., author.
1 online resource
Keywords: World Past to World Present: A Sketch of Global History provides an unusually brief and present-focused treatment of human history beginning with the advent of agriculture and ending with considerable attention to world history developments since World War II. This accessible and concise text covers a very real but selected history of the human experience. The book emphasizes the importance of contacts and exchanges among different cultures and economies up to contemporary globalization, and consistent attention is devoted to comparisons among major regional societies. The characteristics of agricultural, and later industrial, societies help establish a larger framework within the text. Peter N. Stearns works to connect past developments to contemporary global patterns and problems, explicitly balancing major changes with significant continuities. Key features include: A "no-frills" approach to an expansive stretch of human history Encourages students to understand the importance of studying history by focusing on aspects of the past that are particularly useful in assessing the current state of the world Invites instructors to combine the advantages of systematic summary coverage with varied supplementary reading Nine maps illustrate important movements and civilizations throughout the world. Truly international in coverage, this book has been specifically designed as a core text for Global History survey courses.